The Pharmacological Inhibition of CaMKII Regulates Sodium Chloride Cotransporter Activity in mDCT15 Cells - Mohammed F. Gholam; Benjamin Ko; Zinah M. Ghazi; Robert S. Hoover; Abdel A. Alli (Biology, 2021)
The thiazide-sensitive sodium chloride cotransporter (NCC) in the distal convoluted tubule is responsible for reabsorbing up to one-tenth of the total filtered load of sodium in the kidney. The actin cytoskeleton is thought to regulate various transport proteins in the kidney but the regulation of the NCC by the actin cytoskeleton is largely unknown. Here, we identify a direct interaction between the NCC and the cytoskeletal protein filamin A in mouse distal convoluted tubule (mDCT15) cells and in the native kidney. We show that the disruption of the actin cytoskeleton by two different mechanisms downregulates NCC activity. As filamin A is a substrate of the Ca2+/calmodulin-dependent protein kinase II (CaMKII), we investigate the physiological significance of CaMKII inhibition on NCC luminal membrane protein expression and NCC activity in mDCT15 cells. The pharmacological inhibition of CaMKII with the compound KN93 increases the active form of the NCC (phospho-NCC) at the luminal membrane and also increases NCC activity in mDCT15 cells. These data suggest that the interaction between the NCC and filamin A is dependent on CaMKII activity, which may serve as a feedback mechanism to maintain basal levels of NCC activity in the distal nephron.